Poorly Crystalline Fe (III) Oxide excess can to alter the electrochemical paths of soils in the Brazilian Tropical Savannah. - Pessoa-de-Souza, Marco Aurélio; Assis, Paula Camylla Ramos; Salgado, Fabrício Henrique Moreira; da Silva, Luciana Gomes; de-Campos, Alfredo Borges; Anunciação, Carlos Eduardo; Moreira, Alisson Neves Harmyans; Fernandes, Eliana Paula (Multi-Science Journal, 2018)
Fe oxides are the one of the major constituents of tropical soils, and have very reactive and binding sites. Under flooding conditions used as electron acceptors in respiration of anaerobic microorganisms. The aim of this study was to present the electrochemical and microbiological behavior of a tropical hydromorphic soil under application of Poorly Crystalline Fe(III) oxide. In this way, an iron gel solution was prepared in three different concentrations (0.001, 0.01, 0.03 M) and distributed in four blocks in a microcosm assay. Electrochemical measurements and assessments of soil microbial biomass was made in four different periods (1, 7, 15 and 30 days). Fe (III) oxide changes the pH, Eh and microbial biomass until 15 days of incubation. The 0.03 M concentration prolonged the buffering system, and apparently was change the microbiota more abruptly, on the other hand, at the final incubation, are suggest the development of specific groups capable to degrade crystalline iron.